Project manager’s competency framework in managing Industrialised Building System (IBS) construction project. / Izatul Laili Jabar - Jabar, Izatul Laili (Institute of Graduate Studies, UiTM, 2017)
Industrialised Building System (IBS) has been introduced to promote a systematic construction process. The application of IBS offers numerous benefits such as cost and time reduction and enhancing construction quality and safety. In the Malaysian construction industry, IBS application was also expected to minimise the dependency on unskilled foreign labour. There are various issues associated with IBS construction projects such as poor quality building and construction delay, and thus, a qualified and experienced organisation led by a competent project manager is required to overcome the issues. The project manager who possesses the necessary competencies may lead the project to success and achieve its objectives. The objectives of this research are to investigate the competencies required for a project manager in managing IBS construction project; to determine the competencies required within the project management phases; to analyse the most significant competencies within the project management phases and to develop a competency framework for a project manager in managing the IBS construction project…